Optimization of metabolite extraction protocols for untargeted metabolite profiling of mycoparasitic Scytalidium parasiticum using LC-TOF-MS - Lim, Choon Kiat; Rafidah Ahmad,; Nurul Fadhilah Marzuki,; Goh, Yit Kheng; Kamalrul Azlan Azizan,; Goh, You Keng; Goh, Kah Joo (Penerbit Universiti Kebangsaan Malaysia, 2018)
Basal stem rot disease of oil palm caused by Ganoderma boninense is one of the most devastating diseases in oil palm plantation resulting in low yield, loss of palm stands and shorter replanting cycle. To-date, there is no effective treatment for Ganoderma infected palms. Control measures, either chemical or cultural approaches, show varying degrees of effectiveness. The application of biological control agents which is environmental-friendly could be an attractive solution to overcome the problem. Earlier, we had isolated a mycoparasite, Scytalidium parasiticum, from the basidiomata of Ganoderma boninense. In vitro assay and nursery experiment showed that this fungus could suppress Ganoderma infection and reduce disease severity. However, metabolites which might contribute to the antagonistic or mycoparasitic effect remain unknown. In the current study, optimization of fungal sample processing, extraction, and analytical procedures were conducted to obtain metabolites from the maize substrate colonized by mycoparasitic ascomycetous Scytalidium parasiticum. This technique capable of producing sexual spores in sac-like organs. Untargeted metabolomics profiling was carried out by using Liquid Chromatography Time of Flight Mass Spectrometry (LC-ToF-MS). We found that S. parasiticum in both liquid- and solid-state cultivation gave higher metabolite when extracted with 60% methanol with 1% formic acid in combination with homogenisation methods such as ultrasonication and grinding. The findings from this study are useful for optimisation of metabolite extraction from other fungi-Ganoderma-plant interactions.